Mitophagy receptor FUNDC1 regulates mitochondrial dynamics and mitophagy. Issue 4 (2nd April 2016) - Chen, Ming; Chen, Ziheng; Wang, Yueying; Tan, Zheng; Zhu, Chongzhuo; Li, Yanjun; Han, Zhe; Chen, Linbo; Gao, Ruize; Liu, Lei; Chen, Quan
ABSTRACT: Mitochondrial fragmentation due to imbalanced fission and fusion of mitochondria is a prerequisite for mitophagy, however, the exact "coupling" of mitochondrial dynamics and mitophagy remains unclear. We have previously identified that FUNDC1 recruits MAP1LC3B/LC3B (LC3) through its LC3-interacting region (LIR) motif to initiate mitophagy in mammalian cells. Here, we show that FUNDC1 interacts with both DNM1L/DRP1 and OPA1 to coordinate mitochondrial fission or fusion and mitophagy. OPA1 interacted with FUNDC1 via its Lys70 (K70) residue, and mutation of K70 to Ala (A), but not to Arg (R), abolished the interaction and promoted mitochondrial fission and mitophagy. Mitochondrial stress such as selenite or FCCP treatment caused the disassembly of the FUNDC1-OPA1 complex while enhancing DNM1L recruitment to the mitochondria. Furthermore, we observed that dephosphorylation of FUNDC1 under stress conditions promotes the dissociation of FUNDC1 from OPA1 and association with DNM1L. Our data suggest that FUNDC1 regulates both mitochondrial fission or fusion and mitophagy and mediates the "coupling" across the double membrane for mitochondrial dynamics and quality control.